2022
DOI: 10.1049/hve2.12259
|View full text |Cite
|
Sign up to set email alerts
|

Thermal ageing of soft and hard epoxy resins

Abstract: Two kinds of epoxy resin, a soft one with rubber‐based additives and an ordinary hard one, are used as electrical insulators and airtight sealants in electrical penetrations in nuclear power plants (NPPs). Knowing how they behave under adverse environments is important for the safe operation of NPPs. In this regard, we gave artificial thermal ageing treatment to the two resins by heating them in air at various temperatures. The resins were then subjected to mechanical, thermal, and dielectric tests. As a resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…In the Japanese example above, cross-linked polyethylene (XLPE), flame-retardant (FR) XLPE, FR cross-linked polyolefin (XLPO), FR ethylene propylene diene rubber (EPDM), silicone rubber, and soft and hard epoxy resins have been systematically investigated [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In the Japanese example above, cross-linked polyethylene (XLPE), flame-retardant (FR) XLPE, FR cross-linked polyolefin (XLPO), FR ethylene propylene diene rubber (EPDM), silicone rubber, and soft and hard epoxy resins have been systematically investigated [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In Japan, we have been carrying out various research projects, entrusted by the Secretariat of the Nuclear Regulation Authority in Japan, on XLPE, 9,10 FR-XLPE, 11,12 FR-EPDM, 13,14 FR-XLPO, 15,16 SiR, [17][18][19][20][21][22][23][24] and two kinds of epoxy resins. 3,4,25 As a result, the following findings have been obtained for sheet-shaped SiR samples. When SiR is treated thermally or concurrently with heat and radiation, it forms cross-linked structures via the oxidation of Si atoms that follows the loss of the pendant CH 3 groups.…”
Section: Introductionmentioning
confidence: 64%
“…In Japan, two kinds of epoxy resins, soft and hard, are used as the resin. 3,4 The integrity of the electric insulation of such cables or penetrations is generally based on type approval for the specified operating period. On the other hand, the most common operation periods of cables are 30 to 40 years in many industrial sectors.…”
Section: Introductionmentioning
confidence: 99%
“…(EPDM) [8,9], FR cross-linked polyolefin [10,11], silicone rubber [12,13], and hard and soft epoxy resins [14][15][16] as typical polymeric insulating materials used in safety-related cables and electrical penetrations. As a result of such extensive research, we have found that oxidation and hydrolysis, as well as cross-linking and the breaking of chemical bonds, are fundamental degradation factors common to all of the polymers studied.…”
Section: Superposition Of Time-dependent Datamentioning
confidence: 99%
“…Large-scale research projects are being conducted from this viewpoint in the USA [ 1 , 2 ] and Europe [ 3 , 4 ], as well as in Japan. During the course of the Japanese project, which has been entrusted to us by the Secretariat of the Nuclear Regulation Authority in Japan, we have been conducting much research into the degradation of cross-linked polyethylene (XLPE) [ 5 , 6 ], flame-retardant (FR) XLPE [ 7 ], FR ethylene-propylene-diene rubber (EPDM) [ 8 , 9 ], FR cross-linked polyolefin [ 10 , 11 ], silicone rubber [ 12 , 13 ], and hard and soft epoxy resins [ 14 , 15 , 16 ] as typical polymeric insulating materials used in safety-related cables and electrical penetrations. As a result of such extensive research, we have found that oxidation and hydrolysis, as well as cross-linking and the breaking of chemical bonds, are fundamental degradation factors common to all of the polymers studied.…”
Section: Introductionmentioning
confidence: 99%